Jet rapidity distributions and jet-jet correlation functions. (1st July 2022) - Bethencourt de León, N; Chachamis, G; Sabio Vera, A
Abstract: Multi-particle production studies have always been an important tool in the effort to study the properties of the strong force already from the fifties of the previous century. As the center-of-mass energy of present day hadron colliders and in particular the Large Hadron Collider (LHC) has increased enormously over the years and the focus currently is on the study of multi-jet final states, it would be instructive to see whether the early days phenomenological models applied some 50–60 years ago to describe multi-particle production have anything to offer in the study of multi-jet final states as well as whether they offer predictions different from the QCD based ones. In this paper, we will consider events with two jets well separated in rapidity with similar transverse momenta whereas a number of mini-jets or jets is to be found in between these two bounding jets. Such configurations are relevant for the high energy scattering limit of QCD. We fix the final jet multiplicity to take particular values and we report on a first comparison between the predictions of the old multiperipheral Chew-Pignotti model applied for final state jets and those of BFKL. We compare single jet rapidity distributions as well as jet-jet rapidity correlations.